Etos Kerja Islami Pada Kinerja Bisnis Pedagang Muslim Pasar Besar Kota Madiun - Bagus Mohamad Ramadhan; Muhamad Nafik Hadi Ryandono (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research is aimed to figure out and explain the impact of Islamic work ethics on business performances of Moslem merchants in Pasar Besar in Madiun City. It also become the basic questions for the interview based on the side of the sales turnover, profit, market share and the number of labors.This research used the qualitative research method and case study as the strategy. Data collection was done by interviewing and observing the research object directly. The qualitative explanatory was used as the technique of analysis by explaining the results of the interviews and of the direct observations.The results of this research reveals some significant impacts of the Islamic work ethics on business performances of the Moslem merchants in Pasar Besar Madiun City. Merchants who implemented the values of the Islamic work ethics indicated positive impact of increased turnover, market shares and numbers of labors.